3D digital anatomy modelling – Practical or pretty?. Issue 3 (June 2015) - Murgitroyd, Ellen; Madurska, Marta; Gonzalez, Jasmina; Watson, Angus
Abstract: Background: With an increasing move towards digitalisation of medical records and medical teaching, such as online exams and webinars, one of the questions that persists asks 'is there a place for digital anatomy teaching and can it effectively replace the traditional teaching methods such as cadaveric dissection?' Cadaveric dissection has a number of benefits as a teaching method but it also has its limitations. Although these can be partially addressed by prosections and new more "life-like" fixatives, it does not address the lack of resources and the increasing pressure to be able to study and learn at home. Methods: This paper reviews the literature with regards to the suitability of digital models for teaching and the wider uses a 3D digital anatomy model could have, such as postgraduate teaching, patient education and surgical planning. It also looks briefly at the learning model that anatomy as art contributes. Results: The literature has scattered examples of digital models used for teaching at both undergraduate and postgraduate level, which demonstrate a number of positive outcomes, mostly surrounding user satisfaction and convenience. 3D modelling for patient education and operation planning has less exploration, and these papers generate a number of discussion points, mostly surrounding the practicality of digital models, which can be more time consuming and require the technology to be widely available and reliable. Conclusions: 3D digital anatomy is a useful adjunct to teaching and its use in patient education and operation planning have interesting possibilities still to be fully explored.